MEMBANGUN PERADABAN BANGSA DENGAN PENDIDIKAN KARAKTER - Sri Susanti (Postgraduate Program Magister Pendidikan Agama Islam, 2016)
Progress and development of technology has brought an enormous influence on the norms and value systems of society, human behavior, organization, family structure, the mobility of society, government policies, and so on. Weakness generation to understand and appreciate the moral values and religious teachings cause they do not have a good filter when consumed, adopt, or to absorb foreign cultures. As a result they are more likely to a bad choice of the values of kindness. They have been deprived of religious teachings and moral values and noble values that fact has long been owned by the nation itself. Deterioration of moral values and religion is characterized by the occurrence of a multidimensional crisis that was twisted nation today is inseparable from the negligence of the national education system has been less attention to the formation of national character. Character education is the key to social improvement and the progress of civilization that upholds integrity and human values to achieve a balance between knowledge and morality. Character education can be done through education of religion applied in any academic life. Character education requires an exemplary figure as a role model to enforce values or rules that have been agreed. This is where the role of educators, especially teachers, parents, the community and the government as an exemplary figure so that learners are capable of doing imitation of moral behavior. The integration of Islamic values (al-kariimah morality) in the learning process should be carried out at all stages of learning from the planning stage of learning, learning implementation, and evaluation of learning. Islamic religious education teachers in this regard in cooperation with civic education teachers act as consultants learning for all subject teachers or class teachers to integrate the values of character as well as the values of Islam into all learning activities in schools.